The Dipeptide Pro-Gly Promotes IGF-1 Expression and Secretion in HepG2 and Female Mice via PepT1-JAK2/STAT5 Pathway - Zhang, Mengyuan; Xu, Jingren; Wang, Tao; Wan, Xiaojuan; Zhang, Fenglin; Wang, Lina; Zhu, Xiaotong; Gao, Ping; Shu, Gang; Jiang, Qingyan; Wang, Songbo (Frontiers in Endocrinology, 2018)
It has been shown that IGF-1 secretion is influenced by dietary protein or amino acid. However, whether the dipeptides elicit regulatory effects on IGF-1 secretion remains largely unclear. Thus, this study aimed to investigate the effects of the dipeptide Pro-Gly on IGF-1 expression and secretion in HepG2 cells and mice, and explore the underlying mechanisms. The in vitro results indicated that Pro-Gly, but not Pro plus Gly, promoted the expression and secretion of IGF-1 in HepG2. Meanwhile, the expression of the peptide transporter 1 (PepT1) was elevated by Pro-Gly, whereas knockdown of PepT1 with siRNA eliminated the increase of IGF-1 expression induced by Pro-Gly. In addition, Pro-Gly activated JAK2/STAT5 signaling pathway in a PepT1-dependent manner. Furthermore, Pro-Gly enhanced the interaction between JAK2 and STAT5, and the translocation of phospho-STAT5 to nuclei. Moreover, inhibition of JAK2/STAT5 blocked the promotive effect of Pro-Gly on IGF-1 expression and secretion. In agreement with the in vitro results, the in vivo findings demonstrated that Pro-Gly, but not Pro plus Gly, stimulated the expression and secretion of IGF-1 and activated JAK2/STAT5 signaling pathway in the liver of mice injected with Pro-Gly or Pro+Gly acutely or chronically. Besides, acute injection of JAK2/STAT5 inhibitor abolished the elevation of IGF-1 expression and secretion induced by Pro-Gly in mice. Collectively, these findings suggested that the dipeptide Pro-Gly promoted IGF-1 expression and secretion in HepG2 cells and mice by activating JAK2/STAT5 signaling pathway through PepT1. These data provided new insights to the regulation of IGF-1 expression and secretion by the dipeptides.